PENGARUH PENGENDALIANINTERN, KOMITMEN ORGANISASI, SUMBER DAYA MANUSIA DAN GOOD GOVERNANCETERHADAP KINERJA INSTANSI PEMERINTAH DAERAH (Studi pada Satuan Kerja Perangkat Daerah Kota Pekanbaru dan Kabupaten Kampar) - Putri, Sonia Sischa Eka; Anisma, Yuneita; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of internal control, organizational commitment, human resources, and good governance on the performance of local government in District Government of Pekanbaru city and Kampar. The samples use were as manyas 57 people are respondents. The population in this study is 63 working units Pekanbaru and Kampar district. The type of data used is primary data by using questionnaire method of data collection. The method of data analysis used in this study is multiple regression with the help of software SPSS version 20. The result showed that: (1) Internal Control has significant influence on the performance of local government, (2) Organizational Commitment has significant influence on the performance of local government, (3) Human resources has significant influence on the performance of local government, and (4) Good Governancehas significant influence on the performance government. From all the testingist done it can be concluded that the variables of internal control, organizational commitment, human resources, and good governance that it used to explain 64,4% of performance of local government variables. While there meaning 35,6% are influence do rexplained by other variables not included in this study.Keywords: Internal Control, Organizational Commitment, Human Resources, Good Governance, and performance.